Interleukin-6 treatment enhances human monocyte permissiveness for Paracoccidioides brasiliensis growth by modulating cytokine production - Siqueira, Keila Zaniboni [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP]; Dias-Melicio, Luciane Alarcao [UNESP]; Calvi, Sueli Aparecida [UNESP]; Peraçoli, Maria Terezinha Serrão [UNESP] (Taylor & Francis Ltd, 2009)
The effect of interleukin (IL)-6 on cytokine production was evaluated in human monocyte cultures infected with the virulent strain of Paracoccidioides brasiliensis (Pb18). Peripheral blood monocytes from healthy individuals were preincubated for 24 h with or without human recombinant IL-6, and then challenged with Pb18 for 4 h and 18 h. P. brasiliensis growth was assessed by viable fungi recovery from co-cultures after plating on BHI-agar. Moreover, tumor necrosis factor-alpha (TNF-), IL-6 and IL-10 production in supernatant cultures was determined by enzyme immunoassay (ELISA). Monocyte preincubation with IL-6, and challenged with Pb18 for 4 h, led to significantly higher fungi recovery compared to non-treated co-cultures. The pretreatment of monocytes with IL-6 induced an inhibitory effect on TNF- and IL-10 production during 18 h fungal infection. Otherwise, an autocrine stimulatory effect on IL-6 production was detected at 4 h and 18 h as represented by an elevation in IL-6 levels. The reduction in TNF- levels and stimulation of IL-6 production induced by previous IL-6 treatment might be responsible for a significant increase in fungal growth in human monocytes. The results suggest that IL-6, by exerting a modulatory effect on cytokines production, makes monocyte more permissive for fungal growth.
Keywords: interleukin-6; interleukin-10; monocytes; Paracoccidioides brasiliensis; tumor necrosis factor-alpha